The Development Of Mathematics Handout Based On Local Wisdom Nuanced For Secondary Students - Putri, Hani Rizkia; Ekawati, Rooselyna (Universitas Negeri Surabaya, 2019)
This study aims to develop a mathematics handout based on local wisdom nuanced to increase the mathematical problem-solving skill of the Secondary students. This research is motivated by the students ability to solve the social arithmetic problem. This study used four phases of developmental research such as Investigation, Design, Realization, and Test, Evaluation, and Revision. The characteristics of local wisdom were acquired within the design or context in the mathematics handout to develop secondary students problem-solving skills. The results show that the students do the stages of problem-solving by Polya, get the maximum score and show students positive responses in the questionnaire given. Therefore, it met the proper handout criteria such as valid, practice, and effective. In the future studies, we encouraged to develop learning materials which have a guide to do phases of problem-solving and apply the way to solve some problems in mathematics.